"Activography": a novel, versatile and easily adaptable method for monitoring enzymatic activities in situ. Issue 22 (3rd March 2017) - Pampalakis, G.; Zingkou, E.; Vekrellis, K.; Sotiropoulou, G.
Abstract : We developed activography to map enzymatic activities on tissue sections using activity-based probes. Abstract : We developed activography to map enzymatic activities on tissue sections using activity-based probes. The assay was validated using a new protease-activity probe on skin biopsies to provide proof-of-concept. Activography is more selective and technically easier than the established in situ zymography, thus, adaptable in routine running clinico-chemical laboratories.